Measuring distortions to agricultural incentives for value chain analysis: Evidence from Indian value chains - Tokgoz, Simla; Majeed, Fahd (John Wiley & Sons, 2019)
We extend the nominal rate of protection (NRP) methodology to a value chain framework. We develop our methodology for three types of value chains: a new value chain created by policy, a value chain in which a by‐product is created in the processing of a commodity, and a value chain in which processing of a commodity generates new product(s). We consider two cases of value chains: when the commodity is tradable and when it is non‐tradable. The proposed indicator, value chain NRP, allows policy‐makers to see an aggregate measure of all policy impacts on all the commodities and products in the value chain, normalised at the farm level. We apply the methodology to selected value chains in India. Our results indicate that farmers are subsidised, but at different rates. Both sugarcane producers and sugar producers are protected, but sugar producers are protected at higher rates. Producers of downstream products such as ethanol and molasses are taxed, whereas the crushing industry is subsidised. We observe that there is increasing protection along the value chain from commodity to product for the oilseeds sector, whereas the picture is less clear for the sugarcane value chain.